System of Rice Intensification with Intercropping - Mairaj Shah, Tavseef (2017)
The Climate Food and Farming (CLIFF) Research Network is an international research network that helps to expand young researchers' knowledge and experience working on climate change mitigation in smallholder farming. CLIFF provides grants for selected doctoral students to work with CGIAR researchers affiliated with the Standard Assessment of Mitigation Potential and Livelihoods in Smallholder Systems (SAMPLES) project. This presentation is entitled System of Rice Intensification with Intercropping by Tavseef Mairaj Shah, a scientist with the Institute of Wastewater Management and Water Protection Hamburg University of Technology.